Double Linker Triphenylamine Dyes for Dye-Sensitized Solar Cells - Peter Holliman (Energies, 2020)
Most organic dyes synthesized for dye-sensitized solar cells (DSC) use a single linker group to bind to the metal oxide photo-anode. Here we describe the synthesis and testing of two new triphenylamine dyes containing either two carboxylic acids 5-[2-(4-diphenylamino-phenyl)-vinyl]-isophthalic acid (10) or two cyanoacrylic acids (2Z, 2′Z)-3, 3′-(5-((E)-4-(diphenylamino) styryl)-1, 3-phenylene) bis (2-cyanoacrylic acid) (8) as linker groups. Full characterization data are reported for these dyes and their synthetic intermediates. DSC devices have been prepared from these new dyes either by passive or fast dyeing and the dyes have also been tested in co-sensitized DSC devices leading to a PCE (η = 5.4%) for the double cyanoacrylate linker dye (8) co-sensitized with D149. The dye:TiO2 surface interactions and dye excitations are interpreted using three modelling methods: density functional theory (at 0 K); molecular dynamics (at 298 K); time dependent density functional theory. The modelling results show the preferred orientation of both dyes on an anatase (1 0 1) TiO2 surface to be horizontal, and both the simulated and experimental absorption spectra of the dye molecules indicate a red shifted band for (8) compared to (10). This is in line with broader light harvesting and Jsc for (8) compared to (10).